2001
DOI: 10.1128/jvi.75.13.6209-6211.2001
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Interleukin-8 in Serum Are Associated with Hepatitis C Virus Infection and Resistance to Interferon Therapy

Abstract: Hepatitis C virus (HCV), a major cause of liver disease worldwide, is frequently resistant to the antiviral alpha interferon (IFN). We have recently found that the HCV NS5A protein induces expression of the proinflammatory chemokine IL-8 to partially inhibit the antiviral actions of IFN in vitro. To extend these observations, in the present study we examined the relationship between levels of IL-8 in serum, HCV infection, and biochemical response to IFN therapy. Levels of IL-8 were significantly elevated in 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
160
1
6

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(177 citation statements)
references
References 18 publications
8
160
1
6
Order By: Relevance
“…12,13,15,16 These data suggest that serum levels of cytokines, such as IL-8, TNF-α, and TGF-β1, might be important predictors of the virologic response to HCV therapy. In the present analysis, we measured cytokine levels to determine if cytokine expression was also associated with HCV virologic, histologic, or biochemical response among HCV/HIV-coinfected persons.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…12,13,15,16 These data suggest that serum levels of cytokines, such as IL-8, TNF-α, and TGF-β1, might be important predictors of the virologic response to HCV therapy. In the present analysis, we measured cytokine levels to determine if cytokine expression was also associated with HCV virologic, histologic, or biochemical response among HCV/HIV-coinfected persons.…”
Section: Discussionmentioning
confidence: 94%
“…4 There is growing evidence that cytokine expression is also linked to HCV treatment response, with lower baseline levels generally correlated with virologic response. [4][5][6][7][8][9][10][11][12][13] Thus, certain cytokines may be useful as easily measured, predictive markers of treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…IFN-γ is clearly augmented in the serum of chronic hepatitis C patients (Tilg et al 1992, Cacciarelli et al 1996, Kamal et al 2004) and its increase has been correlated with an increase in the severity of disease (Gonzalez-Peralta et al 1994). Moreover, an increased expression of IL-1, IL-2, IL-6, IL-10 and IL-18 has been documented in either the blood or liver of chronically HCV infected patients (Makris et al 1994, Schvoerer et al 2003, Hassan et al 1997, Oyanagi et al 1999, Polyak et al 2001. Nonetheless, most studies have been limited by a reduced sample size, resulting in a lack of statistical power.…”
Section: Abstract: Chronic Hepatitis C -Cytokines -Immunohistochemismentioning
confidence: 94%
“…The levels of cytokines such as IFN-γ, TNF-α, IL-6 and IL-8 are elevated in individuals with chronic hepatitis C [74][75][76][77][78][79][80][81][82], and some authors have shown that this increase is proportional to the extent of the damage, histologically [26,76,83,84].…”
Section: Cell Response To Hcvmentioning
confidence: 99%